INNOVATIVE ASPECTS OF IMPROVING THE EDUCATIONAL PROCESS IN HIGHER EDUCATION - Boymuradov, Shukhrat; Hodjaeva, Umida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In modern conditions, the wide introduction of information and communication technologies (ICT) into the social sphere is of great importance, therefore the development of science is impossible without the use of new educational technologies.The purpose of the research is to develop scientific and methodological provisions for the use of infocommunication technologies and internationalize professional training of medical students.The object of the research is the process of improving the professional training of students in medical universities.The subject of the research is the pedagogical and organizational-content conditions for improving the information training of students of medical schools on the basis of the use of ICT in teaching.The hypothesis of the research is that increasing the information training of students of medical schools in professional activities based on the use of ICT will be effective if:- the scientifically grounded way of preparation of students for professional activity with use of ICT within the framework of existing State educational standards of the higher vocational training is offered;- a model for the formation of cognitive activity of students of medical schools based on the use of ICT is developed.The methodological basis of the research are the ideas of the theory of a intergral educational process, the concept of personal developmental learning, the concept of education using computer technology, the concept of the formation of the information culture of the individual in general and the teacher, in particular [2,4,5,7,8].Conclusions: The analysis of the state of the development of information technologies in education, the disclosure of the specifics of the use of ICT allow to develop organizational and semantic conditions for the formation of elements of the methodical system of using modern information technologies in vocational training of medical students.